From restoration to regeneration: periodontal aging and opportunities for therapeutic intervention. Issue 1 (October 2016) - Huang, Lan; Salmon, Benjamin; Yin, Xing; Helms, Jill A.
Abstract: With the march of time our bodies start to wear out: eyesight fades, skin loses its elasticity, teeth and bones become more brittle and injuries heal more slowly. These universal features of aging can be traced back to our stem cells. Aging has a profound effect on stem cells: DNA mutations naturally accumulate over time and our bodies have evolved highly specialized mechanisms to remove these damaged cells. Whilst obviously beneficial, this repair mechanism also reduces the pool of available stem cells and this, in turn, has a dramatic effect on tissue homeostasis and on our rate of healing. Simply put: fewer stem cells means a decline in tissue function and slower healing. Despite this seemingly intractable situation, research over the past decade now demonstrates that some of the effects of aging are reversible. Nobel prize‐winning research demonstrates that old cells can become young again, and lessons learned from these experiments‐in‐a‐dish are now being translated into human therapies. Scientists and clinicians around the world are identifying and characterizing methods to activate stem cells to reinvigorate the body's natural regenerative process. If this research in dental regenerative medicine pans out, the end result will be tissue homeostasis and healing back to the levels we appreciated when we were young.